The Effect of Good Corporate Governance, Internal Control System, and Human Resource Competence on Financial Reporting Quality - Akbar, Aditya; Choiriah, Siti (LifeSciFi, 2025)
This study examines the effect of Good Corporate Governance, Internal Control Systems, and Human Resource Competencies on the Quality of Financial Statements, with Professionalism as a moderating variable. The population of this study consists of Rural Bank companies registered with the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in the J and T regions. The study employs a purposive sampling method, targeting respondents who work in the accounting department of Rural Banks, with a minimum of one year of experience. Data collection is conducted through a direct approach using a questionnaire, targeting 78 respondents, who serve as research subjects. The collected data is processed using SmartPLS version 4 software as a data analysis tool. The results indicate that Good Corporate Governance and Human Resource Competencies significantly affect the Quality of Financial Statements, whereas the Internal Control System does not. Additionally, Professionalism, as a moderating variable, strengthens the relationship between Good Corporate Governance and the Internal Control System with the Quality of Financial Statements. However, Professionalism does not moderate the relationship between Human Resource Competencies and the Quality of Financial Statements.